(untitled) (Reflection and Critique Law Magazine, 2024)
The presente paper aims to analyze the theme 1.046, judged on June 2, 2022 by the Federal Court of Justice, under the prism of the constitucionals juridic principles. The Brazilian Supreme Court, fixed a thesis, with general repercution that allows that the collective negotiations (Collectives agreements and Collectives Conventions), that includes workers unions, removes labor rights even if there are no compensatory benefits in a context where those Unions offer just na underrepresentation. This decision does not allow the application of a series of principles not only of labor law (Principle of Protection and Principle of the Most Favorable Rule), but also constitutional principles, such as the right to life, human dignity and the principle of social well-being.